“The features of the pedagogical department activities in Odessa state pedagogical institute named after K.D. Ushynsky (1945-1970) - Bashkir, O. I. (Problems of Engineer-Pedagogical Education, 2018)
The main purpose of teacher education is the training of educational activities subjects and thus the rise in productivity of educational sector of the state as a whole. The activities of the Department of Pedagogy as a leading one in the structure of the higher pedagogical educational institution meet all the requirements of society in the training of future professional teachers. The activities spectrum of the Pedagogical Department of the Odessa State Pedagogical Institute named after K. D. Ushynsky during 1945-1970 is included not only traditional as for the department areas (academic, scientific, educational, organizational), but it also diversified the activities of the educational institution, specialized departments, the Institute of Teachers Advanced Training, teaching staff of schools not only in Odessa and the region but also in the whole Ukraine. There were scientific laboratories, the University of Teachers Advanced Experience, PublicPedagogicalUniversity for parents created on the basis of the Department of Pedagogy. Members of the department regularly communicated with schools, they carried out experimental studies on their bases to improve students' practical training. Distinguishing the features of the activities the Department of Pedagogy of the Odessa State Pedagogical Institute named after K. D. Ushynsky contributes to identify historical foundations of pedagogical ideas, theories, concepts, to assess objectively the known facts, realities, experience of future teachers training in order to improve the educational and scientific potential of Ukrainian society.